Briarenols F–H: New polyoxygenated briarane diterpenoids produced by the octocoral Briareum excavatum. Issue 18 (30th April 2020) - Huynh, Thanh-Hao; Lee, Gene-Hsiang; Fang, Lee-Shing; Sheu, Jyh-Horng; Sung, Ping-Jyun
Graphical abstract: Highlights: New briaranes, briarenols F–H (2 –4 ), were obtained from octocoral B. excavatum . Absolute configuration of excavatolide C (1 ) was determined by X-ray analysis. Excavatolide C (1 ) showed inhibition effect on iNOS release from RAW 264.7. Abstract: Two known briarane diterpenoids, excavatolide C (1 ) and briacavatolide C (5 ), along with three new polyoxygenated analogues, briarenols F–H (2 –4 ), have been isolated from the supercritical CO2 extraction of an octocoral identified as Briareum excavatum . The absolute configuration of 1 was determined by a single-crystal X-ray diffraction analysis for the first time and the structures of 2 –5 were established by spectroscopic methods. Bioactivity study showed that briaranes 1, 4 and 5 showed inhibition effects on iNOS release from RAW264.7.